Perspectives on Learning Disabilities: The Vectors of a New Convergence - Barsch, Ray H. (Journal of Learning Disabilities, 2016)
Learning disabilities is what this Journal is about. In the following article, Dr. Barsch sets forth past, present and possibilities for the future of the field...
5 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1968ZE76300001 tex.unique-id: [object Object]
Keywords: dept.sed

Reading achievement in the middle school years: A study investigating growth patterns by high incidence disability. - Yakimowski, Mary E.; Faggella-Luby, Michael; Kim, Yujin; Wei, Yan (Journal of Education for Students Placed at Risk, 2016)
Numerous research studies (e.g., Anderson, Kutash, & Duchnowski, 2001; Lane, Carter, Pierson, & Glaeser, 2006; Volpe, Dupaul, Jitendra, & Tresco, 2009; Wei, Blackorby, & Schiller, 2011) have shown that students with disabilities generally exhibit lower reading scores than their peers without disabilities. However, questions remain about the possibility of longitudinal differences among high-incidence disability classifications (e.g., speech/language impairments, SLI; emotional disturbances, ED; learning disabilities, LD; and attention deficit disorders, ADD). This study investigated growth patterns in reading achievement among middle school students from 5th to 8th grade with different high incidence disability classifications on one state's high-stakes assessment. After a repeated measures analysis of variance and post hoc testing, results reveal that students identified as LD and SLI evidenced more growth in reading than those classified as either ADD or ED. In light of the No Child Left Behind Act of 2001 legislation, findings about the various growth patterns are discussed with respect to policy, measurement, and practical implications. © 2016 Taylor & Francis Group, LLC.
12 citations (Crossref) [2023-10-31] Citation Key Alias: pop00217 tex.type: [object Object]
Keywords: dept.sed

Common types of reading problems and how to help children who have them - Spear-Swerling, Louise (Reading Teacher, 2016)
Patterns of reading difficulty provide an educationally useful way to think about different kinds of reading problems, whether those problems are mainly experiential in nature (e.g., those common among English learners) or associated with disabilities (e.g., those typical of children with dyslexia). This article reviews research on three common patterns of poor reading: specific word-reading difficulties, specific reading-comprehension difficulties, and mixed reading difficulties. The purpose of the article is to explain how teachers can use assessments to identify individual struggling readers' patterns of reading difficulties, and how this information is valuable in differentiating classroom instruction and planning interventions.
13 citations (Crossref) [2023-10-31] tex.eissn: 1936-2714 tex.unique-id: ISI:000372317700007
Keywords: Diagnostic; Instructional intervention; Instructional strategies; dept.rdg; dept.sed; peer-reviewed; teaching strategies

How Portuguese and American teachers plan for literacy instruction. - Spear-Swerling, Louise; Lopes, Joao; Oliveira, Celia; Zibulsky, Jamie (Annals of Dyslexia, 2016)
This study explored American and Portuguese elementary teachers' preferences in planning for literacy instruction using the Language Arts Activity Grid (LAAG; Cunningham, Zibulsky, Stanovich, & Stanovich, 2009), on which teachers described their preferred instructional activities for a hypothetical 2-h language arts block. Portuguese teachers (N = 186) completed Portuguese versions of a background questionnaire and LAAG electronically, in Survey Monkey; American teachers (N = 102) completed identical English measures using paper and pencil. Results showed that teachers in both groups usually addressed comprehension and reading fluency on their LAAGs and that they also allocated the most time to these two areas. However, American teachers were more likely to include teacher-directed fluency activities, whereas Portuguese teachers were more likely to include fluency activities that were not teacher directed. Significantly more American than Portuguese teachers addressed phonics in their planning, whereas significantly more Portuguese than American teachers addressed writing processes such as revision. Both groups of educators demonstrated large variability in planning, with many teachers omitting important components of literacy identified by researchers, for writing as well as reading. The study highlights the importance of providing teachers with comprehensive, research-based core literacy curricula as well as professional development on key components of literacy. Study findings also suggest significant relationships between orthographic transparency and teachers' instructional planning.
5 citations (Crossref) [2023-10-31] Place: United States Spear-Swerling, Louise. Department of Special Education and Reading, Southern Connecticut State University, 501 Crescent St., New Haven, CT, 06515, USA. SPEARSWERLL1@southernct.edu. Lopes, Joao. School of Psychology, Department of Applied Psychology, University of Minho, Campus de Gualtar, 4710-057, Braga, Portugal. Oliveira, Celia. Lusofona University of Porto, Rua Augusto Rosa, no 24, 4000-098, Porto, Portugal. Zibulsky, Jamie. Psychology Department, T-WH1-01, Fairleigh Dickinson University, 1000 River Road, Teaneck, NJ, 07666, USA.
Keywords: *Language Arts; *Literacy; *School Teachers; *Teacher Training; Adult; Comprehension; Cross-linguistic; Curriculum; Female; Humans; Language Arts; Literacy; Male; Phonetics; Portugal; Reading; School Teachers; Teacher Training; Teacher beliefs; Teacher education; Teacher knowledge; United States; Writing; Young Adult; adult; comprehension; curriculum; dept.rdg; dept.sed; female; human; language; literacy; male; phonetics; school teacher; teacher training; young adult